[ARTICLE WITHDRAWN] Anaerobic Process. (1st October 2016) - Yang, Qian; Ju, Mei‐Ting; Li, Wei‐Zun; Liu, Le; Wang, Yan‐Nan; Chang, Chein‐Chi
Abstract : THIS ARTICLE WAS WITHDRAWN BY THE PUBLISHER IN DECEMBER 2017 OWING TO POTENTIAL PLAGIARISM.